An Antigua Gambling Model for the International Tax Regime - Adam H. Rosenzweig (Washington University Journal of Law & Policy, 2014)
The international tax world is facing a defining moment. While there is little agreement on anything else within the field, there appears to be a wide and deep consensus that the modern international tax regime—the so-called flawed miracle emerging from World War II—is irrevocably broken. Rich countries, poor countries, multinational institutions, scholars, and politicians all seem to agree the time is now to revisit the international tax regime and rebuild it from the ground up. Leading the way is the Organization for Economic Cooperation and Development (OECD) through its Base Erosion and Profit Shifting (BEPS) project, which promises to adopt common international principles to prevent multinational taxpayers from using techniques that cause their income to fall through the cracks without any country able to meaningfully tax it. But the BEPS project, as well as all similar efforts, faces the formidable task of building a consensus without the infrastructure of a new institutional framework for international taxation. Of course, the task of developing an entirely new institutional framework for international tax is a major and daunting one. Rather than address the enormity of this entire project, this Essay will focus on one aspect that has received less attention as of late: even if a consensus around new rules can be universally agreed to, what happens when countries break the rules? This Essay briefly describes the Antigua Gambling dispute and the resolution adopted by the Dispute Settlement Body of the WTO. Then, this Essay briefly describes the state of the modern debate over BEPS and similar projects. This Essay uses Antigua Gambling as a thought experiment of how to build dispute resolution mechanisms for international tax, proposing several potential alternative models that could be adopted.
Keywords: international tax; OECD; BEPS; dispute settlement body; WTO; UIGEA; GATS; TRIPS; retaliatory tariff; cross-retaliation; Antigua; Antigua Gambling; transfer pricing; double tax; territorial exemption; foreign tax credit; comparable sales method; tax competition; gross withholding tax; tradeable credit